The true sale doctrine in asset securitisation: the Nigerian perspective (2019)
The true sale doctrine is the foundation of every securitisation transaction. Assets transferred to a Special Purpose Vehicle in a securitisation transaction can only he bankruptcy remote if the transfer was a true sale transaction. Yet, the doctrine is surrounded by controversies and complexities. While some jurisdictions are using legislation to settle this controversy for the benefit of the investors and the broader economy, the Nigerian position is still unclear, confusing and without direction. This paper is an attempt to draw attention to the significance of true sale as it relates to the sale of receivables in asset securitisation. In doing this this paper considered the Asset Backed Securitisation Act of the United States of American States of Delaware and Texas and English courts position on true sale to underscore the importance of the doctrine This article further considered the position of the Nigerian Securities and Exchange Commission Rules on Securitisation and its limitations with regards to true sale doctrine. The paper concludes that the Nigerian position is not in tandem with international best practices and recommends the enactment of a securitisation law that will specifically address the question of true sale doctrine